(untitled) (Bangladesh Journal of Public Administration, 2021)
Among the legacies of technical assistance in Public Administration to developing countries, the most notable is the network of institutions devoted to training, education and research in the field. The failure of Anzerican Public Administration did not necessarily lead to a rejection of Public Administration as a worthy subject for continued study and research. Rather such a failure was responsible for an intensive search to find out as to what had gone wrong in the field. The outcoine of the process has informed subsequent generation of academicialls and practitioners about the dangers of indiscriminate tlnnsfer of teclmologies developed n the western world to the developing countries. Even when some technologies that may seem relevant will need considerable liodificationp rior to their introductionin a different culture. What has come to be known as "ecology" in Public Administration is considered an important determinant in technology transfer.